The Analysis of Illocutionary of Main Character’s Utterances in Alladin Movie - Ni Luh Putu Nevik Meilasari; I Gusti Ayu Vina Widiadnya Putri (Austronesian: Journal of Language Science & Literature, 2023)
This research presents a description of the speech act. This research identifies the types of illocutionary acts used by the main characters. This research uses a qualitative method—the data obtained from the Alladin movie. The analysis was presented in a formal and informal presentation. Several steps were taken to analyze the data. First, the researcher watches the movie from beginning to end. Second, the researcher takes note of the illocutionary act in the conversation. The last one is the researcher classifying the data based on the types of illocutionary acts. As a result, five illocutionary acts were discovered in the utterances of the main characters in Alladin’s movie. Those are declarative, representative, expressive, directive, commissive. The researcher found five types: directive 3 data or 23%, expressive 3 data or 23%, representative 2 data or 15%, commissive 1 data or 8%, and declarative 4 data or 31% used in the Alladin movie. The most frequent type used was declarative.